Pitx3 controls multiple aspects of lens development - Medina-Martinez, Olga (2009)
The transcription factor Pitx3 is critical for lens formation. Deletions in the promoter of this gene cause abnormal lens development in the aphakia (ak) mouse mutant, which has only rudimentary lenses. In this study, we investigated the role of Pitx3 in lens development and differentiation. We found that reduced expression of Pitx3 leads to changes in the proliferation, differentiation and survival of lens cells. The genetic interactions between Pitx3 and Foxe3 were investigated, as these two transcription factors are expressed at the same time in lens development and their absence has similar consequences for lens development. We found no evidence that these two genes genetically interact. In general, our study shows that the abnormal phenotype of the ak lenses is not due to just one molecular pathway, rather in the absence of Pitx3 expression multiple aspects of lens development are disrupted.